Study on long-term distribution and short-term characteristics of the waves near islands and reefs in the SCS based on observation. (15th December 2020) - Xiaolong, Liu; Zhiwen, Cai; Ze, Sun; Wenwei, Chen; Jun, Yu; Jun, Ding; Yonglin, Ye
Abstract: Islands and reefs in the South China Sea (SCS) have typical characteristics of coral reef topography and geomorphology. Due to the complexity of topography and geomorphology, waves propagating from the deep water area to the islands and reefs area deform much. The short-term characteristics and long-term distribution characteristics of the waves are very different from the deep sea and of great importance to the evaluation of the movement and load of offshore engineering structures. Therefore, this paper takes the typical island and reef area in the South China Sea as an object. On the one hand, based on the field experiment data near the typical islands and reefs in the SCS, three models are applied to obtain the joint distribution of wave heights and periods. Through the comparison, the goodness of data is given and the suitable model for the islands and reefs is put forward. On the basis of the above, the wave environment contour is obtained by using IFORM model to evaluate the joint distribution of wave heights and periods corresponding to different recurrence periods for the specific engineering sea area. On the other hand, starting from the short-term wave behavior, based on the characteristic sea conditions of typhoon waves and waves caused by the northeast monsoon at the fixed point, the wave spectrum characteristics are analyzed to obtain the spectral slope of the high frequency of the wave spectrum, which reveals the difference with that of the deep-water wave spectrum. The results of the above study lay a preliminary foundation for the accurate description of the characteristics of long-term and short-term wave conditions near islands and reefs of the SCS. Highlights: A comparative study is carried out to find a suitable model to describe the joint distribution of wave heights and periods near islands & reefs in South China Sea. The comparison between the maximum significant wave height from the wave contours and the extreme values from the traditional univariate distribution of wave heights gives a reference for engineering applications. There is a seasonal spectral slope in the high frequency of bimodal spectrum near islands and reefs, and it is quite different from that of deep-water wave spectra. Ochi-Hubble spectrum is not suitable for the evaluation of peak frequency of bimodal spectrum, and the Torsethaugen criterion formula is applicable to the separation of the components of mixed waves near islands and reefs.